Aerobics Low Impact terhadap Tekanan Darah pada Penderita Hipertensi - Trihartuty Trihartuty; Pudji Lestari; Elida Ulfiana (Journal of Telenursing (JOTING), 2022)
This study aims to examine the effectiveness of low impact aerobics on blood pressure in patients with hypertension. The method used is a systematic review by browsing articles on the Scopus, ScienceDirect, EBSCO, ProQuest, PubMed and Google Scholar databases based on PRISMA guidelines. The results showed that the intervention of low impact aerobic exercise significantly affected the blood pressure of hypertensive patients. In conclusion, low impact aerobics can improve health-related quality of life and lower blood pressure in hypertensive patients. Keywords: Aerobics, Hypertension, Blood Pressure